Association Between Non-alcoholic Fatty Liver Disease and Risk of Stroke: A Systematic Review and Meta-Analysis - Wang, Meng; Zhou, Ben-Gang; Zhang, Yi; Ren, Xi-Fang; Li, Ling; Li, Bo; Ai, Yao-Wei (Frontiers in Cardiovascular Medicine, 2022)
Background/objectives: Recent observational studies have explored the association between non-alcoholic fatty liver disease (NAFLD) and stroke with controversial results. We therefore performed a meta-analysis to investigate this possible association. Methods: PubMed, EMBASE and Web of Science database were searched from inception until December 2019, and updated on May 2021. Random-effects meta-analyses were performed by generic inverse variance method. Subgroup and sensitivity analyses were also conducted.The PROSPERO registered number of this study is CRD42020167330. Results:Twenty observational (15 cohort, 4 cross-sectional, and 1 case-control) studies with 17060 388 participants were included in the meta-analysis. Meta-analysis of data from 18 studies with 17 031 672 participants has shown that NAFLD was associated with mildly increased risk of stroke (OR = 1.18, 95% CI:1.08-1.30, P = 0.0005). Similar results were observed in most of the subgroup analyses we performed. Sensitivity analyses did not alter these findings. Meta-analysis of data from 3 studies with 29 614 participants has shown that insufficient evidence to support the proposed association between NAFLD-fibrosis and an increased risk of stroke. Conclusions: We found that NAFLD was associated with increased risk of stroke. However, there was insufficient evidence to support the proposed association between NAFLD-fibrosis and an increased risk of stroke. To better understand any association, future well designed prospective studies that take fully account of specific population, type of stroke, and confounding factors are warranted.